Effects of interpersonal sensitivity on depressive symptoms in postgraduate students during the COVID-19 pandemic: Psychological capital and sleep quality as mediators - Liu, Xin; Peng, Lixin; Wang, Zhen; Zeng, Ping; Mi, Yanyan; Xu, Haibo (Frontiers in Psychiatry, 2023)
Background: This study aimed to explore depressive symptoms associated with interpersonal sensitivity, sleep quality, and psychological capital among postgraduates during campus static management after COVID-19 pandemic in China. Methods: The research data were obtained during campus static management (April 10-19, 2022) after COVID-19 arrived again the city in eastern China. We collected data by means of an online questionnaire and the anonymous self-reported questionnaire included the Patient Health Questionnaire, the interpersonal sensitivity subscale of Symptom Checklist-90, the Psychological Capital Questionnaire, and the Pittsburgh Sleep Quality Index. T-test and ANOVA were used for analysis of variance. The PROCESS macro was used to determine the relationship between interpersonal sensitivity and depression, along with the independently and serial mediating role of psychological capital and sleep quality. Results: A total of 2554 postgraduates were included in this study. The prevalence of mild, moderate, and severe depressive symptoms was 30.97%, 6.58%, and 1.45%, respectively. Interpersonal sensitivity was significantly associated with depressive symptoms (direct effect = 0.183, p < 0.001). Between interpersonal sensitivity and depressive symptoms, psychological capital and sleep quality played a single mediating role, respectively (indirect effect = 0.136 and 0.100, p < 0.001, respectively) and a chain mediating role jointly (indirect effect = 0.066, p < 0.001). Conclusion: Interpersonal sensitivity has significant influence on depression of Chinese graduate students. Psychological capital and sleep quality can not only independently mediate the relationship between interpersonal sensitivity and depression, but also co-play a chain mediating role in the pathway from interpersonal sensitivity to depression. Positive psychological interventions and sleep guide may have benefit in alleviating depressive symptoms.